The Absence of Psychiatric C/S/X Perspectives in Academic Discourse: Consequences and Implications - Jones, Nev; Brown, Robyn (Disability Studies Quarterly, 2012)
There is growing recognition that psychiatric consumer, survivor or ex-patient perspectives are not well-integrated into disability studies work and academic discourse more generally. While limited debate has focused on whether the preferred next step is an independent ‘mad studies’ discourse or a disability studies framework more inclusive of c/s/x voices, the broader consequences of this absence have been largely overlooked. The purpose of this review is to highlight three major consequences of the absence of c/s/x voices in US academics: The (1) relatively greater biomedicalization and (2) clinical professionalization of psychiatric disability compared with other forms of disability, and (3) barriers and obstacles to training and advancement in academia for doctoral students and faculty with psychiatric disabilities. Keywords: consumer/survivor movement, disability studies, activist scholarship, disability in higher education